Accumulation of Volatile Fatty Acids from Hydrothermally Treated Strawberry Extrudate through Anaerobic Fermentation at Different pH Values - Antonio Serrano; Egidio Russo; Blanca Chaves-Quesada; Juan Cubero-Cardoso; Ángeles Trujillo-Reyes; Giovanni Esposito; Xiaofan Xu; Fernando G. Fermoso (Agronomy, 2022)
The accumulation of volatile fatty acids (VFAs) through the anaerobic fermentation of organic waste, such as strawberry extrudate, is proposed for this work. A hydrothermal treatment was carried out, and it was proposed to break the complex matrix of the strawberry extrudate to favour the hydrolysis stage of the anaerobic digestion process. The production of volatile fatty acids from treated and untreated strawberry was evaluated by adjusting the pH to 5 and 9. After the hydrothermal treatment of the strawberry extrudate, an increase in the solubilisation of organic matter, such as sugars and phenols, was observed. In the production of VFAs by means of anaerobic digestion of the pretreated strawberry extrudate, a significant increase in the accumulation of volatile fatty acids was demonstrated at a pH of 9 with respect to the untreated strawberry extrudate. In addition, the operational pH also had a strong effect on the individual VFA profile. A stream enriched in acetic acid was obtained at a pH of 9 (around 65% of the VFAs), whereas the operation at a pH of 5 resulted in a more complex composition with a high percentage of propionic acid (29% of the VFAs).